Lower and upper extremity contributions to propulsion and resistance during semi-tethered load-velocity profiling in front crawl swimming - Keller, S.; Olstad, B. H.; Wahl, P. (Journal of Sports Sciences, 2024)
The study estimated lower and upper extremity contributions to whole-body front crawl swimming using semi-tethered load-velocity profiling. Nine female and 11 male (inter)national-level swimmers performed 20 m semi-tethered sprints, each with five progressive loads for lower (leg kicking), upper (arm stroke), and whole-body front crawl movements. The theoretical maximal speed (v0) and load (L0), and active drag (Da) were expressed as a percentage of the sum of both extremities for the movements of each extremity to calculate their contributions. The difference of whole-body values minus the sum of both extremities was used to estimate whole-body reserves. Lower (upper) body contributions were 43.8 ± 2.8% (56.2%) for v0, 37.3 ± 7.1% (62.7%) for L0, and 39.6 ± 5.6% (60.4%) for Da. Statistically significant whole-body reserves were found for v0 (-30.9 ± 3.9%, p < 0.001) and Da (-5.7 ± 11.7%, p = 0.04). V0 reserves correlated very highly with whole-body v0 in males (r = 0.71, p = 0.014) and moderately in females (r = 0.47, p = 0.21). The lower extremities contribute substantially to front crawl load-velocity profiles of highly trained swimmers. Higher sprint swimming speeds are associated with an efficient speed transfer from lower- and upper- to whole-body movement.